Perceptions of Australian and New Zealand clinicians caring for neonates born at the borderline of viability have changed since the 2005 consensus guideline. (28th March 2019) - Hogan, Sara; Lui, Kei; Kent, Alison L
Abstract : Aim: To determine whether clinician and consumer considerations have changed regarding the resuscitation and support of neonates born at the borderlines of viability since the 2005 New South Wales (NSW) and Australian Capital Territory (ACT) consensus guidelines were developed. Methods: A prospective survey based on the hypotheses and scenarios developed in the original NSW and ACT consensus workshop on perinatal care at the borderlines of viability was sent to neonatologists, fetal medicine specialists, clinical midwife and clinical neonatal consultants and consumer representatives in Australia and New Zealand. Four scenarios and 16 questions were used to explore the respondent's views towards different aspects of the management of neonates born at the borderlines of viability. Australian and New Zealand Neonatal Network data from 2013 or NSW/ACT Neonatal Intensive Care Units (NICUS) data from 1998 to 2004 were used to provide outcome data for each scenario. Results: A total of 87% or more of respondents advocated for resuscitation of neonates at 24 and 25 weeks' gestation in 2015. Only 29% (49/169) would agree to parental request not to resuscitate at 25 weeks and only 10% (17/170) at 26 0–6 weeks. The number of perinatal clinical care providers considering resuscitation at 23 5 weeks' gestation increased from 23% in 2005 to more than 50% in 2015. Conclusion: These findings support the development of updated guidelines for the management of neonates in Australia and New Zealand born at the borderlines of viability to reflect the changes in clinical perceptions and management.